1997
DOI: 10.1002/food.19970410209
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and some properties of plastochromanol‐8

Abstract: Conditions suitable for preparative isolation, quantitative separation and determination ofplastochromanol-8 (PC-8), and their mild oxidation products were elaborated. Mild oxidation of PC-8 alone and with gammatocopherol (gamma-T) equimolare mixture by benzoquinone gives four and two new products, respectively. These products give Emmerie-Engel reaction. Four of gamma-T, three of PC-8 and two mixed mild oxidation products were found in linseed (Leu number = 49). It was also found that PC-8 derived from plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 6 publications
4
47
0
1
Order By: Relevance
“…These values are close to results of Olejnik et al 40 and Obranović et al 9 , but a four-fold higher than in the work Choo et al 5 . Such big variations in content of all tocols could be the result of different harvesting locations and varieties, extraction technologies or storage time of flaxseed oil 5, 9, 37 .…”
Section: Content Of Bioactive Compounds In Fresh Axseed Oilssupporting
confidence: 74%
See 1 more Smart Citation
“…These values are close to results of Olejnik et al 40 and Obranović et al 9 , but a four-fold higher than in the work Choo et al 5 . Such big variations in content of all tocols could be the result of different harvesting locations and varieties, extraction technologies or storage time of flaxseed oil 5, 9, 37 .…”
Section: Content Of Bioactive Compounds In Fresh Axseed Oilssupporting
confidence: 74%
“…In turn, α-tocopherol has strong antioxidant activity in the human body, while the activity of β, γ and Δ homologues is limited because they are immediately metabolized in the liver and excreted in the bile or urine 44 . However, it was shown that plastochromanol-8 has activity even 1.5 times greater than α-tocopherol 40 .…”
Section: Content Of Bioactive Compounds In Fresh Axseed Oilsmentioning
confidence: 99%
“…Compared with vte2 vte1, the presence of PC-8 in vte2-1 prevented lipid oxidation during seed desiccation (15)(16)(17)(18)(19)(20) and early quiescence (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Lipid oxidation is enhanced in vte2-1 seed (and seedlings derived thereof) only after extended quiescence (60 DAP; Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the properties and functions of tocopherols and tocotrienols are widely described in plants, cyanobacteria, and animals (22-24) just a single report has shown that PC-8 is a lipidsoluble antioxidant in vitro (25), and there are no data describing PC-8 function in vivo. To assess PC-8 function in vivo, we generated an Arabidopsis vte2 vte1 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Plastochromanol-8 is considered to be a natural γ-T3 homologue, the only difference being that it has a longer side chain . According to Olejnik et al (1997), the antioxidant properties of PC-8 are 1.5 times greater than those of α-T. Plant sterols form the majority of the unsaponifiable components of most plant oils. The overall quantity of sterols in '00' rapeseed oil varies between 0.45% and 1.13%.…”
Section: Introductionmentioning
confidence: 99%